EFEKTIVITAS MEDIA DADU DALAM MEMPERKENALKAN HURUF HIJAIYAH KEPADA ANAK USIA DINI DI TAMAN KANAK-KANAK ISLAM KHAIRA UMMAH - Anella, Yulastri; Pransiska, Rismareni (Jurnal Caksana : Pendidikan Anak Usia Dini, 2021)
Abtract This research was to determine the development of children's reading skills in recognizing hijaiyah letters through the dice media at kindergarten islamic khaira ummah.This research begins with the assumption that the dice media can help the development of language, especially in the ability to read children in recognizing hijaiyah letters. Researchers found that the media used by teachers in developing the ability to read hijaiyah letters of children at kindergarten islamic khaira ummah.This research used quantitative research with experimental methods in the forms of quashi experimental. The population is the students of Islamic Khaira Ummah, class B6 as an experimental class while B7 as a control class. Each sample consist of 15 children. Research was using cluster sampling technic and this research was using action research and documentation to collect the data. the average reading ability of children's skills in recognizing hijaiyah letters in early childhood in the experimental class was 87,3 and the control class was 82,6, while the result of the effect size with cohen's is 0,895 > 0,80. These results concluded that the effective dice media to develop the ability to read children recognize letters hijaiyah in early childhood.